Estudo audiométrico em trabalhadores de uma indústria de beneficiamento de caroço de algodão da região noroeste do estado de São Paulo - Cabrera Vuolo, Roseliz Abud (2005)
Hearing is a sensory function that allows you to experience sound experiences and develop the language that provides interaction between people and between them and the environment. The auditory sensation affects the psychosomatic state of human beings, influences their professional activity and determines their productive capacity, constituting a relevant socio-economic factor. The multiplication of sources of sound emission and the advent of the industrial revolution, without the proper valuation of the auditory function, resulted in the great current difficulty in ensuring the population's protection against one of the worst aggressors of hearing: noise. Populations exposed to noise show increased morbidity and mortality due to the greater propensity of people to stress and psychosomatic diseases. Noise mainly affects workers exposed to unhealthy sound conditions in the workplace, where the high intensity of environmental noise and prolonged daily exposure cause them to present a clinical picture characterized by noise-induced hearing loss (PAIR), which is currently one of the major public health problems. In order to verify the prevalence of the effect of occupational noise on hearing, audiometric examinations of 100 workers in a cotton processing industry, male, aged 20 to 60 years and service time up to 30 years were analyzed. The examinations were performed after a minimum auditory rest period of 14 hours; the workers were submitted to anamnesis, inspection of the external auditory canal and the determination of the auditory thresholds by the airways (in the frequencies of 250, 500, 1000, 2000, 3000, 4000, 6000 and 8000Hz) and bone (in the frequencies of 500, 1000 , 2000, 3000 and 4000Hz) in both ears. The results showed significant hearing loss, suggestive of PAIR, in 39% of the workers examined (p <0.05), 34% with audiometric notch and 27% with normal hearing. There is a significant worsening of hearing loss (p <0.05) with increasing age of workers. The audiograms showed that the hearing loss also worsens with the increase in the length of service (p <0.05). It is concluded that: the harmful effect of occupational noise is more intense the older the age and the longer the service time of the workers. There is a need for greater awareness among workers, industries and the general population about the harmful effects of noise on the body, because, although there are regulations for prevention, the prevalence of hearing loss, suggestive of PAIR, is still very high.